2021
DOI: 10.1155/2021/5561999
|View full text |Cite
|
Sign up to set email alerts
|

Manual Acupuncture at ST37 Modulates TRPV1 in Rats with Acute Visceral Hyperalgesia via Phosphatidylinositol 3-Kinase/Akt Pathway

Abstract: Acupuncture can significantly ameliorate inflammatory pain in acute visceral hyperalgesia. Hyperalgesia is attenuated by inflammatory mediators that activate transient receptor potential vanilloid 1 (TRPV1), and TRPV1 is regulated by nerve growth factor (NGF)-induced phosphatidylinositol 3-kinase (PI3K)/Akt pathway. However, it is unknown whether NGF-induced PI3K/Akt pathway is associated with manual acupuncture (MA). In this study, the effect and mechanism of MA at Shangjuxu (ST37) and Quchi (LI11) were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Electroacupuncture in ST25 and ST37 can downregulate NGF and TrkA expression in colon tissue of IBS-D model rats ( Yang et al, 2022b ), providing a new avenue for TRPV1 inhibition. In a study involving manual acupuncture treatment of ST37, the NGF-PI3K-TRPV1 axis is presumed to exert a significant influence on colonic hyperalgesia ( Chen C. et al, 2021 ). By initiating and regulating paracrine signals, various types of immune/inflammatory cells present in the intestinal mucosa, laminae propria, and smooth muscle, including leukocytes, lymphocytes, macrophages, dendritic cells, and mast cells (MCs), can influence the Enteric Nervous System (ENS) and vagus nerve fibers, thus producing visceral pain ( Grundy et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…Electroacupuncture in ST25 and ST37 can downregulate NGF and TrkA expression in colon tissue of IBS-D model rats ( Yang et al, 2022b ), providing a new avenue for TRPV1 inhibition. In a study involving manual acupuncture treatment of ST37, the NGF-PI3K-TRPV1 axis is presumed to exert a significant influence on colonic hyperalgesia ( Chen C. et al, 2021 ). By initiating and regulating paracrine signals, various types of immune/inflammatory cells present in the intestinal mucosa, laminae propria, and smooth muscle, including leukocytes, lymphocytes, macrophages, dendritic cells, and mast cells (MCs), can influence the Enteric Nervous System (ENS) and vagus nerve fibers, thus producing visceral pain ( Grundy et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…TRPV1 plays a crucial role in the transmission and modulation of pain signals in both the peripheral and central nervous system, and it also plays a significant role in the development of inflammation-induced thermal hyperalgesia. Upon stimulation by neurotransmitters, endogenous mediators, and inflammatory mediators such as bradykinin, NF-κB, COX-2, PGE2, and TNF-α, TRPV1 is effectively recruited and activated [ 29 32 ]. Building upon our previous research, which demonstrated that A. officinarum flavonoids can regulate TRPV1 receptor expression to protect against gastric mucosal injury [ 8 ], it was hypothesized that through its interaction with the TRPV1 receptor, galangin inhibits the production and release of neurotransmitters, endogenous mediators, and inflammatory mediators, thereby regulating the activity of inflammatory signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…As a typical mechanical stimulation, MA can activate non-selective mechanosensitive ion channels in the cell membrane during needling and regulate the conduction of needling signals, some key mechanotransducers, such as TRPV1 ( Chen et al, 2018 ), TRPV2 ( Huang et al, 2018 ), Piezo1, and Piezo2 ( Guo et al, 2022 ), are involved in the regulation process. It was also found that the expression of related ion channel proteins exhibits varying degrees of stimulation intensity dependence ( Chen et al, 2018 ; Chen C. et al, 2021 ). In contrast, this effect can be blocked by non-selective mechanosensitive channel blockers such as gadolinium ( Varani et al, 2009 ).…”
Section: Stimulation Parameters Of Ma For Selectionmentioning
confidence: 99%